(untitled) (Malaysian Management Journal, 2024)
The evolving landscape of global trade and economic cooperation has spurred the establishment of Special Border Economic Zones (SBEZs) as a comprehensive strategy to catalyse economic growth and enhance collaboration between neighbouring countries. These zones have developed as a distinctive economic strategy to harness the potential of cross-border collaboration, while addressing the particular socio- economic difficulties of border regions as globalisation continues to change the dynamics of global commerce and investment. However, the main challenge to such an effort is understanding how to fully tap the potential of the SBEZs to facilitate cross-border trade, drive economic development, and advance regional integration while simultaneously minimising potential hazards and unfavourable effects. This article provides an in-depth analysis of the relationship between Malaysia and Thailand and the relevance of a SBEZ between the two neighbors. It aims to pursue these objectives: (1) To delve into the historical trajectory of economic progress in the relationship between Malaysia and Thailand, (2) To critically examine the importance of the SBEZs in the Malaysia-Thailand context from various aspects, and (3) To critically evaluate the SBEZs by comparing the economic development of Malaysia and Thailand and by analysing the factors that led to the Thailand-Malaysian SBEZ. Content analysis was used to analyse the secondary data obtained from journals, publications, and official reports. The findings are as follows: 1) There have historically been several economic periods in the relationship between Malaysia and Thailand; 2) In the Malaysia-Thailand region, Special Border Economic Zones are significant in terms of their role in trade facilitation, economic growth, investment, industrialisation, and regional economic balance; and 3)Three factors had an effect on the development of the SBEZs.